Project Report on Detection of MIS-Behaving Nodes in a Mobile AD-Hoc Network - SANTOSH C, PUTTARAJU K S, KARTHIK C S and LOKESH P (2009)
INTERNAL GUIDE: GAYATHRI, MVJCE
Keywords: Mobile AD-Hoc Network